Clinical features of pulmonary arterial hypertension associated with systemic sclerosis - Tuhy, Tijana; Hassoun, Paul M. (Frontiers in Medicine, 2023)
Systemic sclerosis is an autoimmune disorder of the connective tissue characterized by disordered inflammation and fibrosis leading to skin thickening and visceral organ complications. Pulmonary involvement, in the form of pulmonary arterial hypertension and/or interstitial lung disease, is the leading cause of morbidity and mortality among individuals with scleroderma. There are no disease-specific therapies for pulmonary involvement of scleroderma, and pulmonary arterial hypertension in this cohort has typically been associated with worse outcomes and less clinical response to modern therapy compared to other forms of Group I pulmonary hypertension in the classification from the World Symposium on Pulmonary Hypertension. Ongoing research aims to delineate how pathologic microvascular remodeling and fibrosis contribute to this poor response and offer a window into future therapeutic targets.